"Vicious Circle" of War: Metaphorization of Russia’s Invasion of Ukraine in Éric Zemmour’s Twitter Communication - Siden, Olena (Studia Philologica, 2024)
In the crucible of conflict, the discourse employed by political leaders transcends the mere conveyance of information, delving into the realm of strategic communication and persuasion. Twitter, with its brevity and widespread usage among political actors, offers a rich source for investigating political discourse dynamics. Particularly notable is the pervasive use of metaphors by politicians during times of crisis, a linguistic phenomenon that extends beyond its conventional literary function to assume a critical role in shaping public perceptions, fostering unity, and framing the narrative of conflict. This article focuses on the analysis of political communication of Éric Zemmour, a prominent figure in the contemporary French political landscape, on Twitter to reveal main functions of metaphors during the first year of the Russian full-scale invasion of Ukraine. The research has been conducted using Critical Discourse Analysis (CDA) as the main approach and elements of Conceptual Metaphor Theory (CMT). By integrating these methodologies, the study revealed that Éric Zemmour employs conceptual and traditional metaphors to present to explain relations between France-Ukraine-Russia, enhance own credibility and trustworthiness, shape public opinion, simplify the complex geopolitical event, evoke emotional responses, appeal to the national pride and identity, construct social actors and events, underscore the urgency and seriousness of the current situation, and personify the subjects. The paper thus provides a more nuanced understanding of the linguistic and conceptual mechanisms of metaphors in Zemmour’s Twitter communication during a crucial geopolitical event.